2005
DOI: 10.1167/iovs.04-0760
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Array Characterization of 80 Chemokines, Cytokines, and Growth Factors in Open- and Closed-Eye Tears: Angiogenin and Other Defense System Constituents

Abstract: MAs are powerful tools for differential screening of tears for large numbers of trace proteins. Analysis allowed the identification of previously undetected proteins that may participate in the host defense system as well as demonstrated the profound change in tear composition associated with prolonged eye closure in a manner reflective of physiological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 56 publications
6
92
0
3
Order By: Relevance
“…However, it is conceivable that reflex tearing occurs upon awakening as a protective mechanism to wash out unwanted substances accumulated during subclinical ocular inflammation as a result of overnight eye closure. 23 It has been shown that tear meniscus height increases immediately after eye opening in the morning and recovers to baseline approximately 30 minutes after awakening. 24 As tear meniscus height is directly related to tear aqueous volume on the ocular surface, one can presume that the increase in tear meniscus height is because of reflex tearing upon eye opening in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is conceivable that reflex tearing occurs upon awakening as a protective mechanism to wash out unwanted substances accumulated during subclinical ocular inflammation as a result of overnight eye closure. 23 It has been shown that tear meniscus height increases immediately after eye opening in the morning and recovers to baseline approximately 30 minutes after awakening. 24 As tear meniscus height is directly related to tear aqueous volume on the ocular surface, one can presume that the increase in tear meniscus height is because of reflex tearing upon eye opening in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Возрастной диапазон был выбран в соответствии с периодом риска возникновения глаукомы. Мы модифицировали методику, описанную Sack и коллегами [15] Данный препарат в дальнейшем именуется "экзосомы", в отличие от "супернатанта СЖ".…”
Section: выделение субмикроскопических структур из слёзной жидкостиunclassified
“…В СЖ были обнару-жены (50-100%) практически все исследованные цитокины, как правило, в концентрациях, пре-вышавших их уровни в СК. В целом это соот-ветствовало данным литературы о «нормальном» цитокиновом профиле СК и СЖ [1,6,7,8,20].…”
Section: результатыunclassified